Study of Synchronization between Fractional-Order Chaotic Systems via Matrix Projective Method - Shukla, Vijay K. (Discontinuity, Nonlinearity, and Complexity, 2026)
This article studied matrix projective synchronization (MPS) between chaotic systems with hyperbolic nonlinearity. The sufficient conditions for achieving matrix projective synchronization between coupled integer-order and fractional-order chaotic systems with hyperbolic nonlinearities have investigated. In case of matrix projective synchronization the controllers have designed to synchronize chaotic systems. In addition, numerical simulation is discussed to analyze theoretical study. It is also obtained that numerical results are agreed with theoretical results.